The Suitability of a Greater China Currency Union - Yin-Wong Cheung; Jude Yuen (Center for Economic Studies and ifo Institute (CESifo), 2004)
The study assesses the level of integration among the three Greater China economies (namely China, Hong Kong, and Taiwan) and examines the suitability of a Greater China currency union. Currently, the three economies have extensive trade and investment linkages. Our analyses show that these economies share common long-run and short-run cyclical variations. We also estimate the output costs of relinquishing policy autonomy to form a currency union. The estimated output losses, which depend on, for example, the method used to generate shock estimates, seem to be moderate and are likely to be less than the efficient gains derived from a currency union arrangement.
Keywords: 330; Greater China; trade and investment; common stochastic trend; synchronized and non-synchronized business cycles; output losses; exchange rate regime